Experimental research of extended polarization coherence theorem for nonclassical light - Jara Ortiz, Max (2023)
This thesis reports the experimental display of an extension of the polarization coherence theorem (PCT), a theorem that established a constraint between distinguishability and visibility, two quantities that serve, respectively, as a measure of particle-like and wave-like behavior that may simultaneously appear in interferometric arrangements. While the PCT applies in both quantum and classical regimes, this thesis focuses on the quantum case. The experiments were conducted using single photons. The theoretical extension of the PCT that was submitted to experimental test is much more involved than the original PCT and put several technical challenges. This thesis reports the successful implementation of the experiments. The techniques used could also be employed, with slight modifications, when working with classical light. The general framework, in which our results make a contribution, refers to so-called wave-particle duality and Bohr’s complementarity principle. This is a topic of intensive research that addresses not only foundational issues in quantum mechanics but also practical applications in quantum information science.